Distribution and conservation status of the species of the genus Peperomia (Piperaceae) endemic to Mexico - Eire Ramírez-García; Guido Mathieu; Thorsten Krömer (Flora, 2026)

Endemism Centres of the Five Richest Vascular Epiphyte Families in the Neotropics - Maria Judith Carmona‐Higuita; Glenda Mendieta‐Leiva; Jorge Antonio Gómez‐Díaz; Fabricio Villalobos; Flavio Nunes Ramos; João Pedro Costa Elias; Derio Antonio Jiménez‐López; Alejandro Zuluaga; Bruce Holst; Michael Kessler; Guido Mathieu; Alexander Zizka; et al. (Journal of Biogeography, 2025)
Aim Endemic species, characterised by limited geographic ranges, face a high risk of extinction. The neotropical region harbours diverse ecosystems and a substantial number of endemic species, thus identifying areas of high endemism is crucial for protecting unique and threatened species and ecosystems. Vascular epiphytes—nonparasitic plants that grow on other plants without contact with the soil—exhibit remarkable diversity in the neotropics, with 63% of the global total of ca. 31,000 epiphyte species found in this region. This study aims to describe the endemism centres for the five most species‐rich families of vascular epiphytes. Location Neotropics. Taxon Tracheophyta. Methods We gathered information from free‐access web repositories, specific epiphytic plant databases and scientific and grey literature on epiphyte species of the families Araceae, Bromeliaceae, Orchidaceae, Piperaceae and Polypodiaceae within the neotropical realm as defined by Morrone et al. (2022). Geographical ranges were calculated using minimum convex polygons for 11,446 species, accounting for about 70% of all epiphyte species in the neotropics. Narrow endemic species were defined as those within the first quartile of the density distribution of geographic range sizes within each family and we identified endemism centres for epiphyte species of the five families. Results Our study identified endemism centres for vascular epiphyte species in several biogeographic provinces, including Paramo, Cauca, Guatuso‐Talamanca, Atlantic, Yungas and Puntarenas‐Chiriqui. Orchidaceae, accounting for most of the analysed species (71%), drove the overall distribution pattern; however, endemism patterns varied among families. Main Conclusions Regions with high epiphyte richness exhibited a greater proportion of endemic species, though the composition of epiphyte species varied considerably among regions. The endemism centres identified in this study could be prioritised as conserved and protected areas.

Conservation status of vascular epiphytes in the neotropics - Maria Judith Carmona-Higuita; Glenda Mendieta-Leiva; Jorge Antonio Gómez-Díaz; Fabricio Villalobos; Flavio Nunes Ramos; João Pedro Costa Elias; Derio Antonio Jiménez-López; Alejandro Zuluaga; Bruce Holst; Michael Kessler; Guido Mathieu; Alexander Zizka; et al. (Biodiversity and Conservation, 2024)

Consensus Recommendations for Clinical Outcome Assessments and Registry Development in Ataxias: Ataxia Global Initiative (AGI) Working Group Expert Guidance - Thomas Klockgether; Matthis Synofzik; Saud Alhusaini; Mathieu Anheim; Irina Antonijevic; Tee Ashizawa; Luis Bataller; Mélanie Berard; Enrico Bertini; Sylvia Boesch; Pedro Braga-Neto; Emanuel Cassou; et al. (The Cerebellum, 2023)
To accelerate and facilitate clinical trials, the Ataxia Global Initiative (AGI) was established as a worldwide research platform for trial readiness in ataxias. One of AGI’s major goals is the harmonization and standardization of outcome assessments. Clinical outcome assessments (COAs) that describe or reflect how a patient feels or functions are indispensable for clinical trials, but similarly important for observational studies and in routine patient care. The AGI working group on COAs has defined a set of data including a graded catalog of COAs that are recommended as a standard for future assessment and sharing of clinical data and joint clinical studies. Two datasets were defined: a mandatory dataset (minimal dataset) that can ideally be obtained during a routine clinical consultation and a more demanding extended dataset that is useful for research purposes. In the future, the currently most widely used clinician-reported outcome measure (ClinRO) in ataxia, the scale for the assessment and rating of ataxia (SARA), should be developed into a generally accepted instrument that can be used in upcoming clinical trials. Furthermore, there is an urgent need (i) to obtain more data on ataxia-specific, patient-reported outcome measures (PROs), (ii) to demonstrate and optimize sensitivity to change of many COAs, and (iii) to establish methods and evidence of anchoring change in COAs in patient meaningfulness, e.g., by determining patient-derived minimally meaningful thresholds of change.

Anchoveta Engraulis ringens along the Chilean coast: Management units, demographic units and water masses: Insights from multiple otolith‐based approaches - Cristóbal Garcés; Edwin J. Niklitschek; Guido Plaza; Francisco Cerna; Mathieu Leisen; Pamela Toledo; Fernando Barra (Fisheries Oceanography, 2019)
Three management units (MUs) are used for stock assessment and fishery regulations of anchoveta Engraulis ringens in Chilean waters (>65% of E. ringens latitudinal range): MU‐I [18–25)°S, MU‐II [25–32)°S and MU‐III [32–42)°S. To evaluate whether these three MUs correspond to separate demographic units (DUs), as well as to estimate mixing rates and spatial distribution of these DUs, we combined three types of otolith natural markers: isotopic signatures (δ 13 C and δ 18 O), elemental compositions (Na, Mg, Mn, Sr and Ba) and microstructural indexes. All otolith markers were determined in nuclear and marginal regions of juveniles and adults from cohorts 2012 and 2015. Differences in core region markers indicated spatial segregation between three environmentally distinct nursery areas, probably related to Subtropical Water (MU‐I), Subantarctic Water (MU‐III) and the Subtropical Convergence (MU‐II). Comparison of core and marginal regions, from juvenile and/or adult fish, suggested that adult fish remained nearby nursery areas, separated from fish nursed in other MUs. Nonetheless, ontogenetic migrations from warmer (offshore) nursery habitats to cooler (deeper/more coastal) feeding habitats occurred within MUs. In summary, our results support the consideration of the three MUs as three separate DUs. Estimated mixing rates indicated MU‐II received contributions of 31% from MU‐I and 3% from MU‐III, while complete segregation existed between MU‐I and MU‐III. Such mixing rates between MU‐I and MU‐III seem large enough to justify its further consideration by stock assessment models and management procedures.